2015
DOI: 10.1097/jom.0000000000000304
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter, Endotoxin, and Worker Respiratory Health on Large Californian Dairies

Abstract: Modern California dairy endotoxin exposures and shift length were associated with a mild acute decrease in forced vital capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
3
16
0
Order By: Relevance
“…Personal exposure to endotoxin in PM 2.5 among Californian dairy workers has not been previously reported. Here we show that dairy workers had about five times higher personal exposure to PM 2.5 endotoxin compared to controls, which is similar to Mitchell et al [30] who found total inhalable endotoxin was an order of magnitude higher among the same worker. This is likely the case because dairy facilities have more biogenic sources originating from the animals and daily practices when compared to other non-livestock agricultural settings [21].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Personal exposure to endotoxin in PM 2.5 among Californian dairy workers has not been previously reported. Here we show that dairy workers had about five times higher personal exposure to PM 2.5 endotoxin compared to controls, which is similar to Mitchell et al [30] who found total inhalable endotoxin was an order of magnitude higher among the same worker. This is likely the case because dairy facilities have more biogenic sources originating from the animals and daily practices when compared to other non-livestock agricultural settings [21].…”
Section: Discussionsupporting
confidence: 91%
“…Dairy farm job task also influenced endotoxin exposures in IPM pollutants [29]. In the paper by Mitchell et al [30] exposure to endotoxin in the TSP size fraction and shift-length was associated with decrease in FVC. However, this analysis used a larger dairy worker sample size of 205.…”
mentioning
confidence: 98%
“…Endotoxins have been considered to be one of the main factors contributing to occupational lung diseases and organic dust toxic syndrome (Park et al, 2015). In fact, changes in pulmonary function due to endotoxin exposure have been (Paudyal et al, 2011), dairy workers (GM: 329 EU/m 3 (Mitchell et al, 2015), animal feed and grain workers (GM: 662 EU/m 3 ), and sewage treatment plant workers (GM: 214 EU/m 3 ) (Cyprowski et al, 2015).…”
Section: Endotoxinsmentioning
confidence: 99%
“…Agricultural workers inhalation exposure to dust measured over the work‐shift has been reported from 0.8 to 20 mg per cubic meter (mg/m 3 ) [Donham et al, ; Kullman et al, ; Vogelzang et al, ; Spaan et al, ; Reynolds et al, ; Eastman et al, ; Garcia et al, ; Basinas et al, ; Mitchell et al, ]. Among dairy workers, Kullman et al reported personal exposure geometric mean concentrations of inhalable dust and endotoxin at 1.78 mg/m 3 and 647 endotoxin units per cubic meter (EU/m 3 ).…”
Section: Introductionmentioning
confidence: 99%